Pengaruh Jenis Pelarut Terhadap Jumlah Rendemen dan Kadar Total Flavonoid Ekstrak Kulit Buah Markisa Kuning (Passiflora edulis var. flavicarpa) - Margareta Retno Priamsari; Catur Hana Kristanti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Yellow passion fruit (Passiflora edulis var. flavicarpa) is a perennial plant in the form of a shrub that can spread or spread. Yellow passion fruit peel contains many flavonoid compounds that have potential for antioxidants, anti-inflammatories and antibacterials. The aim of this study was to analyze the effect of the type of solvent on the amount of yield and total flavonoid content of yellow passion fruit peel extract. The extraction method uses remaceration with 96% ethanol and ethyl acetate as solvent. Extract quality control using organoleptic, drying shrinkage, yield calculation and qualitative test of flavonoid compounds. Testing for total flavonoid levels was carried out using the colorimetric method with AlCl3 reagent by UV-Vis spectrophotometry and the wavelength used was 436.4 nm. The standard uses quercetin. The results showed that the yield of yellow passion fruit peel extract with 96% ethanol solvent was 4.43%w/w while ethyl acetate solvent was 2.57%w/w. The total flavonoid content of yellow passion fruit peel extract showed a significant difference (p <0.05) which was analyzed by independent sample t-test, namely with 96% ethanol of 4.23 ± 0.02 mgQE/gram and 13.02 mgQE/gram of ethyl acetate. 89±0.01 mgQE/gram.